The development of English plural marking expressions in Malaysian autistic children - Ahmad Sabri, A'ina Athirah; Mohamed Salleh, Rabiah Tul Adawiyah (2020)
Autism spectrum disorder (ASD) is a neurological disorder characterised by deficits in social, communicative and cognitive skills. Recently, the awareness of autism has increased globally as well as nationally, evidenced by the reported increasing number of parents seeking advice on raising their autistic children. In the Malaysian setting, it is still unclear on how autistic children acquire English in ESL context. Therefore, this paper aims to contribute to closing this gap by investigating how three autistic children acquire English, specifically the English plural structures from the developmentally moderated focus-on form instruction (DMFonf). The three autistic children selected were from a special learning centre and their age range were between 9 to 12 years. They were taught the English plural grammatical structures using DMFonf for 12 weeks. Data were collected through audio and video recording at 4 points; T1 (week 4), T2 (week 8), T3 (week 12) and T4 (week 16). The findings of the study show that DMFonf instructions are effective in assisting the participants to acquire English plurals. The results also show that all participants’ trajectory of plural acquisition follow the developmental stages predicted by Processability Theory.